Conflict resolution between husband and wife in the light of the hermeneutics of biblical proverbs - Chukwuma, Onyekachi G. (HTS teologiese studies, 2020)
Conflicts are commonplace in human relationships. The Bible is replete with narratives and proverbial statements which border on conflict scenarios and conflict resolution strategies. Conflict cannot be severed from relationships between biological brothers and sisters, Christians, friends, colleagues and husbands and wives. In this qualitative study, the researchers examined the menace ‘conflict between husbands and wives’. There is no husband and wife relationship which is devoid of disputes and conflicts. In husband and wife relationship, conflict situations could arise from lack of sexual discipline, lack of sexual satisfaction, finance, lack of communication and other areas. The thrust of this article was to examine conflict resolution principles in the light of biblical proverbs. Biblical proverbs refer to concise and wise sayings in the Bible, which give pieces of advice about everyday life. This article utilised the descriptive research methodology to analyse the primary (Bible) and secondary (Internet materials, journal articles and books) data. The major finding of this work are numerous biblical proverbs which are veritable means for resolving conflicts between husbands and wives.Contribution: The article brought to fore the major factors which lead to conflict between husbands and wives. The authors exegetically studied the chosen proverbs in order to ascertain its relevance to conflict situations. The major contribution of this article is that the messages of certain proverbs in the Book of Proverbs are very useful in resolving conflicts between husbands and wives.